2013
DOI: 10.1177/1545968313491012
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Pursuit Eye Movement Training Promotes Recovery From Auditory and Visual Neglect

Abstract: Repetitive contralesional, smooth pursuit training induces superior, multimodal therapeutic effects in mild and severe neglect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 41 publications
1
48
0
12
Order By: Relevance
“…Therefore, the positive effects found here were specific to visuomotor feedback training and are not simply due to non-specific factors (e.g., amount of training or attention received) or conventional rehabilitation therapy. In addition, even though the effects were found with a relatively small sample size of 20 patients, it is important to note that this sample size is still amongst the largest ever reported in any neglect rehabilitation trial, including very recent studies by Kerkhoff et al (2013Kerkhoff et al ( , 2014 showing promising results of "smooth pursuit" training on samples of 50 and 30 patients respectively, and by Mizuno et al (2011) reporting prism adaptation effects in ADL on a sample of 38 patients.…”
Section: Improvements Associated With Treatmentmentioning
confidence: 93%
“…Therefore, the positive effects found here were specific to visuomotor feedback training and are not simply due to non-specific factors (e.g., amount of training or attention received) or conventional rehabilitation therapy. In addition, even though the effects were found with a relatively small sample size of 20 patients, it is important to note that this sample size is still amongst the largest ever reported in any neglect rehabilitation trial, including very recent studies by Kerkhoff et al (2013Kerkhoff et al ( , 2014 showing promising results of "smooth pursuit" training on samples of 50 and 30 patients respectively, and by Mizuno et al (2011) reporting prism adaptation effects in ADL on a sample of 38 patients.…”
Section: Improvements Associated With Treatmentmentioning
confidence: 93%
“…Symptoms often vary from patient to patient due to the heterogeneous nature of visual neglect and its symptoms . The findings from Kerkhoff et al (2013) demonstrated this as effect sizes were greater in those with severe neglect following visual scanning therapy compared to those with mild neglect. Furthermore, these studies excluded patients with any psychological problems such as dementia, limiting the generalizability of the findings from this systematic research review to a specific and potentially very small population.…”
Section: Discussionmentioning
confidence: 82%
“…Two studies (69 participants) used smooth pursuit training (SMT) as an intervention, assessing patient outcomes immediately and two weeks after treatment (Kerkhoff et al, 2013;Kerkhoff et al, 2014). Both studies were of high quality (receiving a PEDro score of 7) using a randomized design where the intervention was administered to patients no more than a month after stroke.…”
Section: Smooth Pursuit Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…A further trial aimed to investigate whether or not smooth pursuit therapy is superior to standard scanning therapy (Kerkhoff et al., 2013). The authors reported more improvement following smooth pursuit training in both auditory and visual outcomes.…”
Section: Interventionsmentioning
confidence: 99%